Isolation of exfoliated boron nitride nanotubes via ethyl cellulose wrapping. Issue 8 (6th February 2021) - De los Reyes, Florencio D.; Fujieda, Tadashi; Takeuchi, Akifumi; Kawai, Tsuyoshi; Nonoguchi, Yoshiyuki
Abstract: Boron nitride nanotubes (BNNTs) are simultaneously isolated and dispersed in organic solvents using a non‐aromatic and highly flexible polymer ethyl cellulose (EC). The colloidal dispersion containing individualized EC‐wrapped BNNTs is stabilized via non‐covalent functionalization through CH‐π and OH‐π interactions between EC and BNNTs. FESEM, TEM, UV‐VIS, FT‐IR, and TG analyses confirm the efficiency of using a simplified and less destructive method without prior heat treatment to enhance the purity and dispersibility of BNNTs in our designed system. This provides a practical approach to the purification and dispersion of BNNTs from a bulk‐produced source, for the fabrication of materials that require large amount of high‐quality BNNTs. Abstract : Opening two locks with one key! Two major issues—low purity and poor dispersibility—limit the potential of boron nitride nanotubes (BNNTs) for various applications. We design a PolSol system using a non‐conjugated polymer, ethyl cellulose (EC). EC wraps then retains the BNNT in the dispersion after mixing and centrifugation that enhances both their purity and dispersibility.